The importance of tourism investment in increasing the volume of tourism movement "Case study in the holy city of Karbala (The Peerian Journal, 2024)
The historical record of the holy city of Karbala during ancient periods and up to the present time, witnessed an increasing tourist movement during those periods to visit the shrine of Imam Hussein and his brother Aba al-Fadl al-Abbas, peace be upon them. In addition to other holy sites and places, it is considered one of the most important centers of religious tourism in the world in general and the Islamic world in particular. It is also a tourist city due to its diverse and unique archaeological and natural attractions to be diverse and distinct tourist landmarks. Which makes it a promising tourist center in light of the diversity of available capabilities and makes it a center of attraction for investors and capital. Tourism investment has sought to increase the volume of this movement. Given the functional role of tourism investment through the positive impact it plays in the local economy, by increasing the volume of domestic and foreign tourism, and given the contribution of these investments to revitalizing the local economy of the geographical locations in which they appear and then their positive role in increasing the value of the gross domestic product. The researcher raised the following main question: Does tourism investment in the holy city of Karbala represent a major element in increasing the volume of tourism movement heading to this city?.